The EU's normative power in the eastern neighbourhood: a critical discourse analysis - Pedrosa, Mafalda Inês Infante (2021)
In 2004 and 2007, the European Union (EU) underwent two of its most important enlargements, including countries from the post-soviet space, perceived as less stable, democratic, and developed. This momentum constituted a challenge for the EU, leading to several reforms in its foreign policy, namely the launching of the European Neighbourhood Policy (ENP) in 2004, that included countries from the eastern and southern borders. This policy aimed to create a stable and prosperous neighbourhood, contributing, simultaneously, to the EU’s security. The creation of this policy contributed to the debate on ‘the EU as a different kind of actor’, specifically, the EU as a normative power. Thus, the goal of this dissertation is to study the concept of Normative Power Europe applied to the ENP, more specifically to its eastern dimension, with a focus on democracy. With a post-structuralist approach, we conducted a critical discourse analysis to understand how the EU constructs, through discourse, representations of itself and others, perpetuating power relations. In order to do so, we analysed the main policy documents of the ENP and the Eastern Partnership (EaP), as well as press releases, statements and speeches about the situation in Belarus, Georgia and Ukraine, between 2003 and 2020. This work concludes that the EU discursively constructs representations of itself as a ‘normative power’, a ‘democracy and human rights model’, as ‘responsible’, and as ‘truly European’, and representations of the partner countries as ‘non-normative’, as an ‘existential threat’, as ‘inferior’, as ‘entities that violate universal principles’, and as ‘non-Europeans’.